Diagnosis for New Pedagogical Strategies in Technical and Vocational Training: Education-Employment-Employability Relationship - Carrera-Barragán, Diego Andrés (2024)
This paper develops the objective of diagnosing the pedagogical process in Technical and Professional training in an educational establishment that offers different technical and technological disciplines. The research was carried out under a mixed approach with an explanatory model using the questionnaire and semi-structured interview as information collectiontechniques. The positions of the students regarding their technical choice programs were assumed regarding the relational tendency of their education, employment and employability with the different subjective position of the interviewee. This change in subjective position was promoted to revive the discussion of the results to subsequently carry out methodologicalstrategies focused on the education-employment-employability relationship.